2016
DOI: 10.1038/ajg.2016.405
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcomes in Children Fathered by Men Treated with Anti-TNF-α Agents Before Conception

Abstract: Our results are overall reassuring regarding the safety of paternal preconceptional use of anti-TNF-α agents. The result regarding SGA should, however, be interpreted with caution as we found an increased risk, although not significantly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…In men with RMD who are planning to father a pregnancy, we strongly recommend continuation of HCQ, azathioprine, 6‐mercaptopurine, colchicine, and tumor necrosis factor inhibitors ( ).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…In men with RMD who are planning to father a pregnancy, we strongly recommend continuation of HCQ, azathioprine, 6‐mercaptopurine, colchicine, and tumor necrosis factor inhibitors ( ).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…Some of the included studies also presented results for exposure at any time before conception. Comparison between ‘exposure 3 months prior to conception’ and ‘exposure at any time before conception’ was possible in publications of the Danish registry data ( Larsen et al , 2016 ; Egeberg et al , 2017 ; Nørgaard and Andersen, 2019 ). See Supplementary Table S5 for outcomes after exposures any time before conception.…”
Section: Discussionmentioning
confidence: 99%
“…Eight small studies and one large population-based cohort were identified ( Lamboglia et al , 2009 ; Paschou et al , 2009 ; Saougou et al , 2013 ; Clowse et al , 2015 ; Larsen et al , 2016 ; Hoxha et al , 2017 ; Uyaroglu et al , 2017 ; Lichtenstein et al , 2018 ; Micu et al , 2019 ). In total, 61 males, 121 pregnancies and 372 children were included.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 63/67 had no malformations or were described as 'healthy'. In addition, three cohort studies (7,22,23) reported 432 peri-conceptional paternal exposures to a variety of anti-TNF medications (adalimumab, etanercept, certolizumab and infliximab), reporting no association with adverse pregnancy outcomes or congenital malformations.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%